2010
DOI: 10.1099/ijs.0.013136-0
|View full text |Cite
|
Sign up to set email alerts
|

Planococcus salinarum sp. nov., isolated from a marine solar saltern, and emended description of the genus Planococcus

Abstract: A Gram-positive, non-motile and coccoid-, short rod- or rod-shaped bacterial strain, ISL-16T, was isolated from a marine solar saltern in Korea and its taxonomic position was investigated using a polyphasic taxonomic approach. Strain ISL-16T grew optimally at pH 7.0–8.0, at 30 °C and in the presence of 2 % (w/v) NaCl. Phylogenetic analysis based on 16S rRNA gene sequences showed that strain ISL-16T joined the cluster comprising species of the genus Planococcus. Its 16S rRNA gene sequence contained the same sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 26 publications
2
25
0
Order By: Relevance
“…It exhibited slightly higher 16S rRNA gene sequence similarity values (96.6 and 96.5%) to the type strains of Alteromonas hispanica and Alteromonas genovensis than to S. chungwhensis BH030046 T , and 93.7-96.1% sequence similarity to the type strains of the other Alteromonas species. It has been shown that the 16S rRNA gene sequence similarity may not be necessarily consistent with the topology of phylogenetic trees (Nedashkovskaya et al 2006;Xue et al 2006;Yoon et al 2010), as it the case here. S. chungwhensis BH030046 T exhibited 92.2-94.7% 16S rRNA gene sequence similarity to the type strains of Alteromonas species.…”
Section: Phylogenetic Analysismentioning
confidence: 68%
“…It exhibited slightly higher 16S rRNA gene sequence similarity values (96.6 and 96.5%) to the type strains of Alteromonas hispanica and Alteromonas genovensis than to S. chungwhensis BH030046 T , and 93.7-96.1% sequence similarity to the type strains of the other Alteromonas species. It has been shown that the 16S rRNA gene sequence similarity may not be necessarily consistent with the topology of phylogenetic trees (Nedashkovskaya et al 2006;Xue et al 2006;Yoon et al 2010), as it the case here. S. chungwhensis BH030046 T exhibited 92.2-94.7% 16S rRNA gene sequence similarity to the type strains of Alteromonas species.…”
Section: Phylogenetic Analysismentioning
confidence: 68%
“…The Planococcaceae family contains independent examples of sporulation loss along the branches leading to Filibacter, Caryophanon, Kurthia, and Planomicrobium/Planococcus (5). Further investigations into this family of bacteria may help unravel the complex sporulation pathway from other mechanisms of stress resistance.…”
mentioning
confidence: 99%
“…Further eight isolates (27.6%) were originally found in saline environments, like marine solar salterns ( Planococcus salinarum and Planomicrobium flavidum ) [37], [38], marine sediments ( Kocuria rosea ) [39] or a salt mine ( Marinococcus luteus ) [40], respectively. Planococcus donghaensis , Paracoccus marcusii and Planococcus antarcticus were previously detected in soil material from the Antarctic, from coastal regions in South Korea [41] and in soil of Issyk Kul region in Kyrgyzstan, respectively.…”
Section: Discussionmentioning
confidence: 99%